Education and training monitor 2022 : Germany - (:unkn) unknown (Publications Office of the European Union, 2022)
“The Education and Training Monitor’s country reports present and assess the main recent and ongoing policy development at all education levels in EU Member States. They provide the reader with more in-depth insight of the performance of countries with regard to the EU level targets agreed within the EEA. They are based on the most up-to-date quantitative and qualitative evidence available. Section 1 presents a statistical overview of the main education and training indicators. Section 2 focuses on how the Member State has addressed or is addressing one of its education challenges. Section 3 covers early childhood education and care. Section 4 deals with school education policies. Section 5 covers vocational education and training and adult learning. Finally, Section 6 discusses measures in higher education.“ (editor; BIBB-Doku)
Keywords: S System beruflicher Bildung; 370; Bildungssystem; Allgemeinbildung; Berufsbildungssystem; Bildungsmonitoring; Benchmarking; Indikatoren; Bundesrepublik Deutschland